Role of Laser Produced Silver Nanoparticles in Reversing Antibiotic Resistance in Some MultidrugResistant Pathogenic Bacteria - Hamad, Abubaker H.; Chawsheen, Mahmoud A.; Al-Naqshbandi, Ahmed A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
Silver nanoparticles (Ag NPs) were produced through nanosecond laser in deionized water. These nanoparticles were characterized by UV–VIS spectrometer and transmission electron microscopy. VITEK®2 compact system was used to identify Escherichia coli (ESBL strain) and Staphylococcus aureus (MRSA strain) as multidrug-resistance (MDR) bacteria. The antibacterial activity of Ag NPs, ampicillin (AMP), and their combinations was tested against both bacterial isolates through standard microbiological culturing techniques. Our data show that both of E. coli and S. aureus were highly resistant to AMP. Ag NPs alone reduced growth in both bacterial isolates considerably. Growth declined drastically in both bacteria when AMP was used in combination with Ag NPs. The minimal inhibitory concentration of combined agents for E. coli was 20 µg/ml Ag NPs + 1 mg AMP/ml and for S. aureus was 10 µg/ml Ag NPs + 1 mg AMP/ml. The results show that the Ag NPs have great potentials in enhancing the antimicrobial activities of drugs that used to be ineffective against MDR bacteria. Administering combinations of antibiotic(s) with AgNPs may help in treating patients suffering from infections caused by MDR bacteria. Further in vivo and in vitro investigations are required to evaluate the side effects of these combinations.